Preference of Female College Students in Judging the Body Silhouette of Young Women - SUGITA, Hiroko; TANAKA, Michi; YAMADA, Hiroshi; TAKAHASHI, Yuko; SATO, Yukiko (Journal of Home Economics of Japan, 2001)
In our experiment we asked, .201 female college/junior-college students as subjects to judge body silhouettes that consisted of all possible pairs of ten female junior-college students' photographs. We analyzed the data of the pair-wised comparisons in terms of multidimensional scaling and found that the preference of body silhouettes had two dimensions. A multiple regression analysis was also applied to examine the relationship between the somatometric measures of body silhouettes and the two dimensions of preference. As a result, it was found that female college/junior-college students had a tendency to attach importance to the side of the body when they judged silhouettes and they were likely to prefer a body silhouette having a narrow-angled thinner abdomen, and a thicker bust and hips.